Planning, management and evaluation in human resource development - Ana Chagelishvili; Natia Surmanidze (Reviews of Modern Science, 2022)
The article reviews the role of Human Resource Development Service in human resource development and the scope of its functions. The aim of the paper is also to determine the place of human resources development in management and to review the issues of its evaluation. The importance of strategic development of human resources is also discussed in the second part.